Interleukin-20 inhibits the osteogenic differentiation of MC3T3-E1 cells via the GSK3β/β-catenin signalling pathway. (May 2021) - Chen, Xi; Liu, Yuanbo; Meng, Bowen; Wu, Dongle; Wu, Yilin; Cao, Yang
Highlights: Interleukin-20 promotes MC3T3-E1 cell proliferation. Interleukin-20 inhibits the osteogenic differentiation of MC3T3-E1 cells. Interleukin-20 may function by regulating the GSK3β / β-catenin signalling pathway. Abstract: Objective: To investigate the effects of interleukin-20 (IL-20) on the osteogenic differentiation of MC3T3-E1 cells. Methods: The pre-osteoblast line MC3T3-E1 was treated with different concentrations of IL-20 (0, 2, 20 and 100 ng/mL), and the cell viability was detected by the CCK8 assay. To assess the influence of IL-20 on osteogenic differentiation, alkaline phosphatase (ALP) activity and Alizarin red staining were performed at predetermined times. The expression levels of Runt-related transcription factor 2 (RUNX2), Osterix (Osx), glycogen synthase kinase-3β (GSK-3β) and β-catenin were detected by qRT-PCR and Western blotting analyses. 5 nmol/L lithium chloride (LiCl) was used as GSK-3β inhibitor. Results: IL-20 promoted cell proliferation but decreased ALP activity and mineralization. Moreover, IL-20 downregulated the expression of RUNX2, Osx and β-catenin but upregulated the level of GSK-3β. Conclusions: The results suggest that IL-20 could inhibit the osteogenic differentiation of MC3T3-E1 cells via the GSK3β/β-catenin signalling pathway.